Impact of euthanasia, dissection and postmortem delay on metabolic profile in mouse retina and RPE/choroid. (September 2018) - Zhu, Siyan; Yam, Michelle; Wang, Yekai; Linton, Jonathan D.; Grenell, Allison; Hurley, James B.; Du, Jianhai
Abstract: Metabolomics studies in the retina and retinal pigment epithelium (RPE) in animal models or postmortem donors are essential to understanding the retinal metabolism and to revealing the underlying mechanisms of retinal degenerative diseases. We have studied how different methods of euthanasia (CO2 or cervical dislocation) different isolation procedures and postmortem delay affect metabolites in mouse retina and RPE/choroid using LC MS/MS and GC MS. Compared with cervical dislocation, CO2 exposure for 5 min dramatically degrades ATP and GTP into purine metabolites in the retina while raising intermediates in glucose metabolism and amino acids in the RPE/choroid. Isolation in cold buffer containing glucose has the least change in metabolites. Postmortem delay time-dependently and differentially impacts metabolites in the retina and RPE/choroid. In the postmortem retina, 18% of metabolites were changed at 0.5 h (h), 41% at 4 h and 51% at 8 h. However, only 6% of metabolites were changed in the postmortem RPE/choroid and it steadily increased to 20% at 8 h. Notably, both postmortem retina and RPE/choroid tissue showed increased purine metabolites. Storage of eyes in cold nutrient-rich medium substantially blocked the postmortem change in the retina and RPE/choroid. In conclusion, our study provides optimized methods to prepare fresh or postmortem retina and RPE/choroid tissue for metabolomics studies. Highlights: Euthanasia with CO2 degrades ATP and GTP into purine metabolites only in retina. Euthanasia with CO2 increases amino acids and intermediates in glucose metabolism only in RPE/choroid. Glucose availability and cold temperature are critical to stabilize metabolism during dissection. 80% of metabolites are stable within 1 h in postmortem retina and 8 h in RPE/choroid. Cold nutrient medium partially prevents the metabolite levels from changing in postmortem retina and RPE.